Concepção de uma sequência didática para o ensino/aprendizagem da congruência - Tojo, Benedita Natsuko (2006)
This dissertation has by purpose to investigate how first grade students of the High School appropriate of the congruence conception and utilize it in the proof process. The research was embased in the investigation of: Parzysz (2001) about thought progress for geometry teaching; Machado (2005) about knowledge net; Freudenthal (1973) about local organization for congruence teaching and Balacheff (1988) about kinds of proofs. It was utilized while research methodology, some didatic engineering principle which involved fourteen first grade students of the High School from a public school of the São Paulo State. The analyses of the experimentation showed that the changing process from concrete to the graphic-space contributed to the appropriation of the congruence conception and how this process collaborated, partially, to the passage from empirism to deduction. Other complements in didatic sequence become necessary to that this passage from empirism to deduction renders more widely